Use of Geospatial Technologies to Identify the Impact of Deforestation and its Associate Event (Soil Erosion) in the North-Bilate Watershed, Southern Ethiopia - Semebo , Melese; Tesfay , Alem; Ersino , Alemu; Abide , Melese (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The rapid population growth in Southern Ethiopia's North-Bilate watershed, specifically in the Boyo Lake area, has resulted in widespread deforestation and soil erosion, affecting the livelihood of farmers. Thus, the current study aimed at assessing the effects of land cover change on soil erosion and agricultural land. For this purpose, 2 lands sat ETM images for the years 2000 and 2020 which have 30*30m resolution were used. The main trajectories of land use change are based on five land use classes which are farmland, built-up area, forest, bare land, water, and open area derived from the remotely sensed images. The analysis showed that Bushland and built-up areas increased with a rate of 1.2 and 2.6 ha/year between 2000 and 2020, respectively. On the contrary, woodland, farmland, and bare land had decreased by 0.2, 0.4, and 3.2 ha/year in the same study period. The NDVI value response of the study period clearly shows the highest value for vegetation cover change, as the maximum value was +0.91 in 2000 and the minimum value was -0.38 in 2020. The dramatic expansion of settlements was due to the runoff of farmland, woodland, and bare land within the allotted period due to rapid population growth and migration from the surrounding rural areas, poor land management, and illegal housing. In summary, signs of deforestation and consequent soil erosion due to population growth, agricultural expansion, forest depletion, and mismanagement are leading to reductions in vegetation cover and agricultural productivity. To minimize soil erosion, physical measures such as terracing and dams should be implemented. In addition, to preserve and increase the biodiversity of the study area, the planting of various types of native vegetation and plantation tree species should be carried out with a viable afforestation and reforestation program.